Assessment of stakeholder's perception of Bhutan as a meeting and incentive destination. - Chhimi Yuden (Prince of Songkla University, 2014)
Thesis (M.B.A., Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2013